Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.jcin.2011.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Operator Radiation Dose by a Pelvic Lead Shield During Cardiac Catheterization by Radial Access

Abstract: Pelvic lead shielding is highly effective in reducing operator radiation exposure for radial as well as femoral procedures. However, despite its use, radial access remains associated with a higher operator radiation dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 14 publications
1
24
2
Order By: Relevance
“…To this end, a number of studies have attempted to quantify the differences in radiation exposure between access sites with increasing TR experience, with conflicting results . Given this, we performed a patient‐level, multi‐center, international, collaborative analysis to determine differences in patient radiation exposure in the context of TR access.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, a number of studies have attempted to quantify the differences in radiation exposure between access sites with increasing TR experience, with conflicting results . Given this, we performed a patient‐level, multi‐center, international, collaborative analysis to determine differences in patient radiation exposure in the context of TR access.…”
Section: Introductionmentioning
confidence: 99%
“…Previous randomised prospective studies19 25 that have compared the radial and femoral techniques have shown an average increase in radiation received by the operator of 61.3% in PCI when using the transradial approach. Another study_ENREF_1818 evaluating chest radiation between radial and femoral approaches showed an average operator absorption of 20.9±13.8 mSv in the radial procedure and 15.3±10.4 mSv in the femoral procedure (p<0.001). To analyse a hostile scenario with a SD of 13.8 and 6.45 mSv difference, we calculated a 72 dosimeter sample (24 patients per group) for 80% power and 96 dosimeters per group for a 90% power with an α error of 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…On average, a coronary angiography and angioplasty correspond to patient radiation exposure levels of 300 and 1000 radiographs, respectively 16. Several randomised studies have examined differences between radial and femoral techniques related to this topic; most of their data infer higher fluoroscopy time, but without significance when compared to radiation dose absorbed by the patient derived from the access route 17 18. The literature is relatively scarce when focusing on operator exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Another challenge with transradial coronary procedures is that they are associated with longer fluoroscopy time [45,46]. There have been two randomized controlled trials that have shown increased operator radiation dose with radial compared with femoral access [47,48]. However, these were both single-center studies with a single operator.…”
Section: Zhou Et Al (2007) Unfractionated Heparin 7215mentioning
confidence: 99%